Stabilizing Off-pathway Oligomers by Polyphenol Nanoassemblies for IAPP Aggregation Inhibition - Nedumpully-Govindan, Praveen (Sci Rep, 2016)
Experimental studies have shown that many naturally occurring polyphenols have inhibitory effect on the aggregation of several proteins. Here, we use discrete molecular dynamics (DMD) simulations and high-throughput dynamic light scattering (DLS) experiments to study the anti-aggregation effects of two polyphenols, curcumin and resveratrol, on the aggregation of islet amyloid polypeptide (IAPP or amylin). Our DMD simulations suggest that the aggregation inhibition is caused by stabilization of small molecular weight IAPP off-pathway oligomers by the polyphenols. Our analysis indicates that IAPP-polyphenol hydrogen bonds and π-π stacking combined with hydrophobic interactions are responsible for the stabilization of oligomers. The presence of small oligomers is confirmed with DLS measurements in which nanometer-sized oligomers are found to be stable for up to 7.5 hours, the time frame within which IAPP aggregates in the absence of polyphenols. Our study offers a general anti-aggregation mechanism for polyphenols, and further provides a computational framework for the future design of anti-amyloid aggregation therapeutics.